Peranan Pemberian Decanter Solid terhadap Serapan Hara N, P, K dan Hasil Tanaman Jagung Manis pada Tanah Gambut - Fransisca, Adelia Irma; Suswati, Denah; Junaidi, Junaidi (Soil Science Department, Faculty of Agriculture, Tanjungpura University, 2026)
Sweet corn (Zea mays L.) is a significant upland crop commodity. Peatlands, characterized by nutrient-poor conditions, require soil conditioners for effective sweet corn cultivation. Decanter solid application serves as an alternative to enhance plant nutrient availability. This study aims to evaluate the effect of decanter solid waste on the uptake of nitrogen (N), phosphorus (P), and potassium (K), as well as the yield of sweet corn (Zea mays L.) on Histosols. The research employed a field experiment based on a Completely Randomized Design (CRD) with six treatment levels of decanter solid, ranging from A_0 (control) to A_5 (1100 g/polybag). Data were analyzed using ANOVA (F-test), followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results indicated that the A_3 treatment (700 g/polybag) was the most optimal dose. This dosage significantly increased plant dry weight and the uptake of N and K in the shoots, with increases ranging from 158.59% to 339.3% compared to the control. The application of A_3 decanter solid also resulted in a highly significant increase in crop yield, as evidenced by the weight of cobs (both with and without husks), which increased between 437.4% and 770.07% relative to the control. However, this dosage did not significantly improve P uptake in the shoots. The utilization of decanter solid waste at a dose of 700 g/polybag holds great potential for enhancing the growth and yield of sweet corn on Histosols